Telemetry‐Based Mortality Estimates of Juvenile Spot in Two North Carolina Estuarine Creeks. Issue 2 (28th January 2013) - Friedl, Sarah E.; Buckel, Jeffrey A.; Hightower, Joseph E.; Scharf, Fred S.; Pollock, Kenneth H.
Abstract: We estimated natural mortality rates ( M ) of age‐1 Spot Leiostomus xanthurus by using a sonic telemetry approach. Sonic transmitters were surgically implanted into a total of 123 age‐1 Spot in two North Carolina estuarine creeks during spring 2009 and 2010, and the fish were monitored by using a stationary acoustic receiver array and manual tracking. Fates of telemetered Spot were inferred based on telemetry information from estimated locations and swimming speeds. Potential competitors of age‐1 Spot were assessed through simultaneous otter trawl sampling, while potential predators of Spot were collected using gill nets and trammel nets. The number of inferred natural mortalities was zero in 2009 (based on 29 telemetered Spot at risk) and four in 2010 (based on 52 fish at risk), with fish being at risk for up to about 70 d each year. Catches of potential competitors or predators did not differ between years, and age‐1 Spot were not found in analyzed stomach contents of potential predators. Our estimated 30‐d M of 0.03 (95% credible interval = 0.01–0.07) was lower than that predicted from weight‐based ( M = 0.07) and life‐history‐based ( M = 0.06–0.36) estimates. Our field‐based estimate of M for age‐1 Spot in this estuarine system can assist in the assessment and management of Spot by allowing a direct comparison with M ‐values predicted from fish size or life history characteristics. The field telemetry and statistical analysis techniques developed here provide guidance for future telemetry studies of relatively small fish in open, dynamic habitat systems, as they highlight strengths and weaknesses of using a telemetry approach to estimate M .